Participants' perspective on maintaining behaviour change: a qualitative study within the European Diabetes Prevention Study - White Martin; Moffatt Suzanne M; Penn Linda (BMC, 2008)
Abstract Background The European Diabetes Prevention Study (EDIPS) is an RCT of diet and exercise interventions in people with impaired glucose tolerance. We undertook a qualitative study, nested within the EDIPS in Newcastle-upon-Tyne, UK, aiming to understand the experience of participants who maintained behaviour change, in order to inform future interventions. Methods Participants were purposively sampled, according to success criteria for diet and physical activity change maintenance, and invited to attend individual semi-structured interviews. Fifteen participants completed an interview and reflected on their experience over three to five years. We used the Framework method to analyse the transcribed data. Results Main themes were identified as factors that help (props) and those that hinder (burdens) behaviour change maintenance at different organisational levels: individual (both physical and psychological), social and environmental. Pre-existing physical conditions (such as arthritis) and social demands (such as caring for an ageing relative) hindered, whereas the benefits of becoming fitter and of having social and professional support helped, participants in maintaining behaviour change. Participants' long term experiences highlighted the salience of the continuous change in their physical, social and environmental conditions over time. Conclusion The construct of props and burdens facilitates a holistic view of participants' behaviour. Efforts to encourage behaviour change maintenance should take account of context and the way this changes over time, and should include strategies to address these issues. The experience of participants who maintain behaviour change highlights the challenges for the wider implementation of diabetes prevention strategies. Trial Registration (ISRCTN 15670600)